Dinamika Pasar Kosmetik Halal Di Sumatera Utara: Analisis Perspektif Konsumen Dan Strategi Produsen - Nasution, Akmal Huda; Munthe, Salman; Adhitya, Wisnu Rayhan; Khaira, Imamul; Rahman, Haikal (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2025)
The halal cosmetics industry is experiencing rapid growth, driven by increasing consumer awareness, particularly among Millennial and Gen Z consumers. This study aims to present a holistic analysis of the factors driving consumer purchase intention towards halal cosmetics in North Sumatra and to formulate the strategies implemented by producers in response to market dynamics. Employing an explanatory sequential mixed-methods design, the research combines a quantitative survey of 400 Millennial and Gen Z respondents with qualitative in-depth interviews with seven industry stakeholders. The quantitative analysis utilized Partial Least Squares-based Structural Equation Modeling (PLS-SEM), while the qualitative analysis employed thematic analysis. The results from the structural model analysis demonstrate that consumer purchase intention is strongly and directly influenced by two core psychological pillars: attitude toward halal products and consumer trust, with the model's predictive power reaching 72.4%. Positive attitude is significantly shaped by the individual's level of religiosity and adequate halal knowledge. Trust, conversely, is cultivated by consumer perception of product quality, positive brand image, and the formal assurance of halal certification. A crucial finding confirms that the influence of product quality and brand image on purchase intention is fully mediated by the trust variable. Halal cosmetic producers in North Sumatra acknowledge the dual market demands, where halal certification is a basic prerequisite, while superior product quality is a competitive necessity. Furthermore, digital marketing via influencers and electronic word-of-mouth (e-WOM) is highly effective in building brand image, yet it does not directly foster deep trust, indicating the fragility of digital reputation if not supported by strong product substance. The most significant operational challenge lies in maintaining the integrity and traceability of the halal supply chain from upstream to downstream. The main conclusion of this study is that success in the modern halal cosmetics market demands an integrated strategy that moves beyond regulatory compliance, focusing consistently on enhancing product quality and supply chain transparency to build authentic and sustainable consumer trust.